Informality, violence, and disaster risks: Coproducing inclusive early warning and response systems in urban informal settlements in Honduras - Peters, Laura E. R.; Clark-Ginsberg, Aaron; McCaul, Bernard; Cáceres, Gabriela; Nuñez, Ana Luisa; Balagna, Jay; López, Alejandra; Patel, Sonny S.; Patel, Ronak B.; Van Den Hoek, Jamon (Frontiers in Climate, 2022)
Anticipatory disaster risk reduction (DRR) is an essential human right for the approximately one billion people living in informal settlements who are disproportionately exposed to climate-related hazards due to their high vulnerability. Participatory approaches are recognized as being critical for effective and sustainable disaster prevention, mitigation, and preparation through to response, but research on how to coproduce anticipatory DRR with people living and working in informal settlements is scant. Their exclusion is even more pronounced in challenging contexts, such as those characterized by social-political fragility and violence. As a result, a significant portion of the global population is left behind in best practices tied to global DRR ambitions, with DRR actions working neither with nor for the people most at risk. The signal case of urban informal settlements controlled by territorial gangs in Tegucigalpa, Honduras, illustrates the need for new thinking on how to inclusively mitigate, prepare for, and respond to natural hazard-related disasters. Our research examines the coproduction of early warning systems linked with response capacities for floods and landslides through the case study of the international NGO GOAL’s work across the city with a focus on nine urban informal settlements with high levels of territorial gang violence. We explore how GOAL navigated informality and violent conflict to support the early warning and response system as an inclusive social process rather than a technical exercise. We identify four cross-cutting strategies employed by GOAL in support of local vulnerability reduction and capacity building based on a local systems approach. This research breaks new ground in identifying how to bridge the gap between knowledge and action in designing inclusive and sustainable early warning and response systems together with the millions of people around the world affected by the intersection of informality, violence, and disaster risks.